Elimination or more accurate estimation? Investigation of trends in malaria diagnoses in the Ouest Department of Haiti from 2008 to 2017. - Thomas A Weppelmann; Caroline J Stephenson; Elisha Musih; John B Dame; Marie Y Remy; Robert Nicolas; Michael E von Fricken (PLoS ONE, 2018)
Background According to the 2016 World Malaria Report, the malaria incidence in Haiti declined by > 40% between 2010 and 2015. Though elimination efforts have likely contributed, this time period also corresponded to a national change in diagnostic methods. Methods Monthly reports of aggregated patient data were acquired from five clinics in the Ouest Department of Haiti. Generalized linear models were used to compare the number of febrile patients tested, the number of positive tests, and the proportion of tests that were positive (TRP) before and after the national adoption of rapid diagnostic tests (RDTs). Results Prior to the earthquake when microcopy was used for diagnosis, a total of 1,727 patients with 557 (32.3%) positive; post-earthquake testing was reduced and the TPR was variable; during the post recovery period when RDTs were used exclusivly, a total of 5,132 patients were tested using RDTs, only 83 (1.62%) were positive. Compared to the pre-earthquake period, there was a 69% increase in the number of patients tested (IRR: 1.69; 95% CI IRR 1.59, 2.79), and a 97.0% decrease in the proportion of patients with a positive test result (IRR: 0.03; 95% CI IRR 0.02, 0.04) in the post-recovery period. Conclusions While the decline in malaria indicators between 2010 and 2015 has been cited as evidence of progress towards elimination, these reports derived estimates of the malaria burden in Haiti using two different diagnostic tests. Thus, comparison of these periods in the context of malaria elimination should be made with caution.